Using the health beliefs model to implement mobile puberty health education in Iranian adolescent boys: a randomized controlled trial - Salahshouri, Arash; Raisi-Philabadi, Parvaneh; Ghanbari, Saeed; Stein, Lar; Araban, Marzieh (Frontiers in Public Health, 2024)
Introduction Given boys' low health knowledge and their unhealthy behavior during puberty, which can cause many physical, mental, and psychological problems, it is important to prevent these complications. This study was therefore aimed to determine the efficacy of a mobile health educational intervention based on the Health Beliefs Model (HBM) on Iranian adolescent boys. Materials and methods This randomized controlled trial involved junior high school boys (n = 148) in Iran studying during the 2020–2021 school year. Educational content concerning healthy behaviors during puberty (e.g., the importance of bathing) was developed based on HBM and sent to the intervention group via mobile phone. HBM addresses multiple factors (e.g., perceived disease risk) that explain health behaviors. The intervention was delivered in five sessions over four weeks using real-time Internet communication and texting. The control group did not receive any intervention. One school was randomly selected from each of the four districts of the study site. The schools were then randomized into intervention and control groups. The boys were then randomly selected from each school to participate in the study. Data collected at baseline and 2-month follow-up assessments included demographic information, health knowledge (e.g., physical changes during puberty), health behaviors (e.g., bathing), and HBM constructs (e.g., self-efficacy to perform healthy behaviors). Data analysis was done using the chi-square, independent and paired t-tests, and analysis of covariance (ANCOVA). Results The two groups did not differ in terms of demographic characteristics. Before the intervention, the two groups were slightly different in terms of knowledge, health behavior, and HBM constructs. Following the intervention, the scores of the intervention group improved significantly (p < 0.05). After adjusting for pre-intervention knowledge, HBM, and health behavior scores, the intervention group remained superior to the control group in terms of improvement of knowledge, HBM constructs, and healthy behaviors (p < 0.05). Effect sizes ranged from medium to large (0.25–0.86). Conclusion Mobile phone education based on the HBM is efficacious in encouraging healthy behavior in boys during puberty. Organizations interested in encouraging healthy behaviors in boys should consider the use of such a program.